Smiles, Systems, and Support: How Technology and Workplace Climate Shape Frontline Employee Growth - Murfat, Moh. Zulkifli; Murfat, Moh. Zulfachmi; Mohamad, Mahathir; Anas, Ali (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Frontline employees stand where technology meets human service. This study contributes to HRM scholarship by integrating Job Demands–Resources and Social Exchange theories to explain how technological support and a supportive working environment jointly uphold employee growth in service organizations. Using survey data from 329 Indonesian retail workers and partial-least-square structural-equation-modeling, results reveal that technology enhances growth both directly and through a supportive climate that nurtures trust and engagement. The findings extend socio-technical and JD–R perspectives by illustrating how digital tools become developmental resources only when embedded in caring organizational climates. Managers should treat technology not as automation but as a partner in human capability building through empathy, training, and supportive design.